-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathmeta.tex
562 lines (477 loc) · 26.7 KB
/
meta.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
416
417
418
419
420
421
422
423
424
425
426
427
428
429
430
431
432
433
434
435
436
437
438
439
440
441
442
443
444
445
446
447
448
449
450
451
452
453
454
455
456
457
458
459
460
461
462
463
464
465
466
467
468
469
470
471
472
473
474
475
476
477
478
479
480
481
482
483
484
485
486
487
488
489
490
491
492
493
494
495
496
497
498
499
500
501
502
503
504
505
506
507
508
509
510
511
512
513
514
515
516
517
518
519
520
521
522
523
524
525
526
527
528
529
530
531
532
533
534
535
536
537
538
539
540
541
542
543
544
545
546
547
548
549
550
551
552
553
554
555
556
557
558
559
560
561
562
\chapter{Invitation to Metatheory}
This chapter is meant to serve as a preview, and for motivation to
work through the chapters to come. In the next chapter, we'll move
quickly into ``categorical set theory'' --- which isn't all that
difficult, but which is not yet well known among philosophers. For
the past fifty years or so, it has almost been mandatory for analytic
philosophers to know a little bit of set theory. However, it has most
certainly not been mandatory for philosophers to know a little bit of
category theory. Indeed, most analytic philosophers are familiar with
the words ``subset'' and ``powerset'', but not the word ``natural
transformation'' or ``equivalence of categories''. To what end these
new concepts?
The short answer is that is that category theory (unlike set theory)
was designed to explicate {\it relations} between mathematical
structures. Since philosophers want to think about relations between
theories (e.g.\ equivalence, reducibility) and since theories can be
modeled as mathematical objects, philosophers' aims will be
facilitated by gaining some fluency in the language of category
theory. At least that's one of the main premises of this book. So,
in this chapter, we'll review some of the basics of the metatheory of
propositional logic. We will approach the issues from a slightly
different angle than usual, placing less emphasis on what a theory
says, and more emphasis on relations between theories.
To repeat, the aim of \emph{metatheory} is to theorize about theories.
For simplicity, let's use $M$ to denote this hypothetical theory about
theories. Thus, $M$ is not the {\it object} of our study, it is the
{\it tool} we will use to study other other theories and the relations
between them. In this chapter, I will begin using this tool $M$ to
talk about theories --- without explicitly telling you anything about
$M$ itself. In the next chapter, I'll give you the user's manual for
$M$.
\section{Logical grammar}
\begin{defn} A \emph{propositional signature} $\Sigma$ is a collection
of items, which we call \emph{propositional constants}. Sometimes
these propositional constants are also called \emph{elementary
sentences}, or even \emph{atomic sentences}. However, we will be
using the word ``atomic'' for a different concept.
These propositional constants are assumed to have no independent
meaning. Nonetheless, we assume a primitive notion of identity
between propositional constants; the fact that two propositional
constants are equal or non-equal is not explained by any more
fundamental fact. This assumption is tantamount to saying that
$\Sigma$ is a \emph{bare set} (and it stands in gross violation of
Leibniz's principle of the identity of indiscernibles). \end{defn}
\begin{ass} The \emph{logical vocabulary} consists of the symbols
$\neg ,\wedge ,\vee ,\to$. We also use two further symbols for
punctuation: a left and a right parenthesis.
\end{ass}
\newcommand{\sigsn}{\mathsf{Sent}(\Sigma )}
\begin{defn} Given a propositional signature $\Sigma$, we define the
set $\sigsn$ of $\Sigma$-sentences as follows:
\begin{enumerate}
\item If $\phi\in\Sigma$ then $\phi\in\sigsn$.
\item If $\phi\in\sigsn$ then $(\neg\phi )\in\sigsn$.
\item If $\phi\in\sigsn$ and $\psi\in\sigsn$, then $(\phi\wedge\psi )
\in\sigsn$, $(\phi\vee\psi )\in\sigsn$, and $(\phi\to\psi
)\in\sigsn$.
\item Nothing is in $\sigsn$ unless it enters via one of the previous
clauses.
\end{enumerate}
The symbol $\phi$ here is a variable that ranges over finite strings
of symbols drawn from the alphabet that includes $\Sigma$, the
connectives $\neg ,\wedge ,\vee, \to$, and (when necessary) left and
right parentheses ``$($'' and ``$)$''. We will subsequently play it
fast and loose with parentheses, omitting them when no confusion can
result. In particular, we take a negation symbol $\neg$ always to
have binding precedence over the binary connectives.
Note that each sentence is, by definition, a finite string of symbols,
and hence contains finitely many propositional constants.
\end{defn}
Since the set $\sigsn$ is defined inductively, we can prove things
about it using ``proof by induction.'' A proof by induction proceeds
as follows: \begin{enumerate}
\item Show that the property of interest, say $P$, holds of the
elements of $\Sigma$.
\item Show that if $P$ holds of $\phi$, then $P$ holds of $\neg \phi$.
\item Show that if $P$ holds of $\phi$ and $\psi$, then $P$ holds of
$\phi\wedge \psi$, $\phi\vee \psi$, and $\phi\to
\psi$. \end{enumerate} When these three steps are complete, one may
conclude that all things in $\sigsn$ have property $P$.
%% TO DO: parse trees
\begin{defn} A \emph{context} is essentially a finite collection of
sentences. However, we write contexts as sequences, for example
$\phi _1,\dots ,\phi _n$ is a context. But $\phi _1,\phi _2$ is the
same context as $\phi _2,\phi _1$, and is the same context as $\phi
_1,\phi _1,\phi _2$. If $\Delta$ and $\Gamma$ are contexts, then we
let $\Delta ,\Gamma$ denote the union of the two contexts. We also
allow an empty context. \end{defn}
\section{Proof theory} \label{sec:pt}
We now define the relation $\Delta\vdash \phi$ of derivability that
holds between contexts and sentences. This relation is defined
\emph{recursively} (aka, \emph{inductively}), with base case
$\phi\vdash\phi$ (Rule of Assumptions). Here we use a horizontal line
to indicate that if $\vdash$ holds between the things above the line,
then $\vdash$ also holds for the things below the line.
\begin{tabular}{l l l}
\textbf{Rule of Assumptions} & \begin{tabular}{c}
\mbox{ } \\
\hline
$\phi \RA \phi$ \end{tabular} \\ \\
{\bf $\wedge$ elimination} & \begin{tabular}{l}
$\Gamma \vdash \phi \wedge \psi$ \\
\hline
$\Gamma \vdash \phi$ \end{tabular} & \begin{tabular}{l}
$\Gamma \vdash \phi \wedge \psi$ \\
\hline
$\Gamma \vdash \psi$ \end{tabular} \\ \\
{\bf $\wedge$ introduction} & \begin{tabular}{l}
$\Gamma \vdash \phi \qquad \Delta \vdash \psi$ \\
\hline
$\Gamma ,\Delta \vdash \phi \wedge \psi$ \end{tabular} \\ \\
{\bf $\vee$ introduction} & \begin{tabular}{l}
$\Gamma \vdash \phi$ \\
\hline
$\Gamma \vdash \phi \vee \psi$ \end{tabular} &
\begin{tabular}{l}
$\Gamma \vdash \psi$ \\
\hline
$\Gamma \vdash \phi \vee \psi$ \end{tabular} \\ \\
{\bf $\vee$ elimination} & \multicolumn{2}{l}{ \begin{tabular}{l}
$\Gamma \RA \phi\vee\psi \qquad \Delta ,\phi \RA \chi \qquad \Theta ,\psi
\RA \chi$ \\
\hline $\Gamma ,\Delta ,\Theta \RA \chi$ \end{tabular} } \\ \\
{\bf $\to$ elimination} & \begin{tabular}{l}
$\Gamma \RA \phi\to \psi \qquad \Delta \RA \phi$ \\
\hline $\Gamma ,\Delta \RA \psi$ \end{tabular} \\ \\
{\bf $\to$ introduction} & \begin{tabular}{l}
$\Gamma ,\phi \RA \psi$ \\
\hline $\Gamma \RA \phi \to \psi$ \end{tabular} \\ \\
{\bf RA} & \begin{tabular}{l}
$\Gamma ,\phi \RA \psi\wedge\neg\psi$ \\
\hline $\Gamma \RA \neg\phi$ \end{tabular} \\ \\
{\bf DN} & \begin{tabular}{l}
$\Gamma\RA\neg\neg\phi$ \\
\hline $\Gamma\RA\phi$ \end{tabular}
% \\ \\
% $\forall$ elimination & \begin{tabular}{c}
% $\Gamma \RA \forall x\phi (x)$ \\
% \hline $\Gamma \RA \phi (a)$ \end{tabular} \\ \\
% $\forall$ introduction & \begin{tabular}{ccc}
% $\Gamma \RA \phi (a)$ & & \multirow{3}{*}{$a$ does not occur in
% $\Gamma$ or $\phi (x)$} \\\cline{1-1}
% $\Gamma \RA \forall x\phi (x)$ \end{tabular} \\ \\
% $\exists$ introduction & \begin{tabular}{c}
% $\Gamma \RA \phi (a)$ \\
% \hline $\Gamma \RA \exists x\phi (x)$ \end{tabular} \\ \\
% $\exists$ elimination &
% \begin{tabular}{ccc}
% $\Gamma \RA \exists x\phi (x) ,\quad \Delta ,\phi (a)\RA \psi$ & & \multirow{3}{*}{$a$ does not occur in
% $\Gamma$, $\Delta$, $\phi (x)$ or $\psi$} \\\cline{1-1}
% $\Gamma ,\Delta \RA \psi$ \end{tabular} \\ \\
% $=$ elimination &
% \begin{tabular}{c}
% $\Gamma \RA \phi (a),\quad \Delta \RA a=b$ \\
% \hline $\Gamma ,\Delta \RA \phi (b)$ \end{tabular} \\ \\
% $=$ introduction &
% \begin{tabular}{c}
% \mbox{ } \\
% \hline $\RA a=a$ \end{tabular}
\end{tabular}
\bigskip The definition of the turnstyle $\vdash$ is then completed by
saying that $\vdash$ is the smallest relation (between sets of
sentences and sentences) such that
\begin{enumerate}
\item $\vdash$ is closed under the clauses above, and
\item If $\Delta \vdash \phi$ and $\Delta \subseteq \Delta '$ then
$\Delta '\vdash \phi$.
\end{enumerate}
The second property here is called \emph{monotonicity}.
There are a variety of ways that one can explicitly generate pairs
$\Delta ,\phi$ such that $\Delta\vdash\phi$. A method for doing such
is typically called a \emph{proof system}. We will not explicitly
introduce any proof system here, but we will adopt the following
definitions.
\begin{defn} A pair $\Delta ,\phi$ is called a \emph{sequent} or
\emph{proof} just in case $\Delta \vdash \phi$. A sentence $\phi$
is said to be \emph{provable} just in case $\vdash\phi$. Here
$\vdash\phi$ is shorthand for $\emptyset \vdash \phi$. We use
$\top$ as shorthand for a sentence that is provable, for example,
$p\to p$. We could then add as an inference rule ``$\top$
introduction'' that allowed us to write $\Delta\vdash \top$. It can
be proven that the resulting definition of $\vdash$ would be the
same as the original definition. We also sometimes use the symbol
$\bot$ as shorthand for $\neg\top$. It might then be convenient to
restate RA as a rule that allows us to infer $\Delta\vdash\neg\phi$
from $\Delta,\phi\vdash\bot$. Again, the resulting definition of
$\vdash$ would be the same as the original. \end{defn}
\begin{disc} The rules we have given for $\vdash$ are sometimes called
the \emph{classical propositional calculus} or just the
\emph{propositional calculus}. Calling it a ``calculus'' is meant
to indicate that the rules are purely formal, and don't require any
understanding of the meaning of the symbols. If one deleted the DN
rule, and replaced it with Ex Falso Quodlibet, the resulting system
would be the \emph{intuitionistic propositional calculus}. However,
we will not pursue that direction at present. \end{disc}
\section{Semantics}
\begin{defn} An \emph{interpretation} (sometimes called a
\emph{valuation}) of $\Sigma$ is a function from $\Sigma$ to the set
$\{ \mathrm{true},\mathrm{false} \}$, i.e.\ an assignment of
truth-values to propositional constants. We will usually use $1$ as
shorthand for ``true'', and $0$ as shorthand for ``false''.
Clearly, an interpretation $v$ of $\Sigma$ extends naturally to a
function $v:\sigsn\to \{ 0,1\}$ by the following clauses:
\begin{enumerate}
\item $v(\neg \phi )=1$ if and only if $v(\phi )=0$.
\item $v(\phi\wedge\psi )=1$ if and only if $v(\phi )=1$ and $v(\psi )=1$.
\item $v(\phi\vee\psi )=1$ if and only if either $v(\phi )=1$ or
$v(\psi )=1$.
\item $v(\phi\to\psi )=v(\neg\phi\vee
\psi)$. \end{enumerate} \end{defn}
\begin{disc} The word ``interpretation'' is highly suggestive, but it
might lead to confusion. It is sometimes suggested that elements of
$\sigsn$ are part of an uninterpreted calculus without intrinsic
meaning, and that an intepretation $v:\Sigma\to \{ 0,1\}$ endows
these symbols with meaning. However, to be clear, $\sigsn$ and
$\{ 0,1\}$ are both mathematical objects; neither one of them is
more linguistic than the other, and neither one of them is more
``concrete'' than the other.
This point becomes even more subtle in predicate logic, where we
might be tempted to think that we can interpret the quantifiers so
that they range over all actually existing things. To the contrary,
the domain of a predicate logic interpretation must be a {\it set},
and a set is something whose existence can be demonstrated by ZF set
theory. Since the existence of the World is not a consequence of ZF
set theory, it follows that the World is not a set. (Put slightly
differently: a set is an abstract object, and the World is a
concrete object. Therefore, the World is not a set.) \end{disc}
%% valuations = possible worlds
\begin{defn} A \emph{propositional theory} $T$ consists of a signature
$\Sigma$, and a set $\Delta$ of sentences in $\Sigma$. Sometimes we
will simply write $T$ in place of $\Delta$, although it must be
understood that the identity of a theory also depends on its
signature. For example, the theory consisting of a single sentence
$p$ is different depending on whether it's formulated in the
signature $\Sigma = \{ p\}$, or in the signature
$\Sigma '=\{ p,q\}$. \end{defn}
\begin{defn}[Tarski truth] Given an interpretation $v$ of $\Sigma$,
and a sentence $\phi$ of $\Sigma$, we say that $\phi$ is \emph{true}
in $v$ just in case $v(\phi )=1$. \end{defn}
\begin{defn} For a set $\Delta$ of $\Sigma$ sentences, we say that $v$
is a \emph{model} of $\Delta$ just in case $v(\phi )=1$, for all
$\phi$ in $\Delta$. We say that $\Delta$ is \emph{consistent} if
$\Delta$ has at least one model, and that $\Delta$ is
\emph{inconsistent} if it has no models.
Any time we define a concept for sets of sentences (e.g.\
consistency), we can also extend that concept to theories, as long
as it's understood that a theory is technically a pair consisting of
a signature and a set of sentences in that signature. \end{defn}
\begin{disc} The use of the word ``model'' here has its origin in
consistency proofs for non-euclidean geometries. In that case, one
showed that certain non-euclidean geometries could be translated
into models of Euclidean geometry. Thus, it was argued, if
Euclidean geometry is consistent, then non-euclidean geometry is
consistent. This kind of maneuver is what we now call a \emph{proof
of relative consistency}.
In our case, it may not be immediately clear what sits on the
``other side'' of an interpretation, because it's certainly not
Euclidean geometry. What kind of mathematical thing are we
interpreting our logical symbols into? The answer here --- as will
become apparent in Chapter \ref{cat-prop} --- is either a Boolean
algebra, or a fragment of the universe of sets. \end{disc}
\begin{defn} Let $\Delta$ be a set of $\Sigma$ sentences, and let
$\phi$ be a $\Sigma$ sentence. We say that $\Delta$
\emph{semantically implies} $\phi$, written $\Delta\vDash \phi$,
just in case $\phi$ is true in all models of $\Delta$. That is, if
$v$ is a model of $\Delta$, then $v(\phi )=1$. \end{defn}
\begin{exercise} Show that if $\Delta,\phi\vDash \psi$, then
$\Delta\vDash\phi\to\psi$. \end{exercise}
\begin{exercise} Show that $\Delta\vDash\phi$ if and only if
$\Delta\cup \{ \neg \phi \}$ is inconsistent. Here $\Delta\cup \{
\neg \phi \}$ is the theory consisting of $\neg\phi$ and all
sentences in $\Delta$. \end{exercise}
We now state three main theorems of the metatheory of propositional
logic.
\begin{thm}[Soundness] If $\Delta\vdash\phi$ then
$\Delta\vDash\phi$. \end{thm}
The soundness theorem can be proven by an argument directly analogous
to the substitution theorem below. We leave the details to the
reader.
\begin{thm}[Completeness] If $\Delta\vDash\phi$ then
$\Delta\vdash\phi$. \end{thm}
The completeness theorem can be proven in various ways. In this book,
we will give a topological proof via the Stone duality theorem (see
Chapter \ref{cat-prop}).
\begin{thm}[Compactness] Let $\Delta$ be a set of sentences. If every
finite subset $\Delta _F$ of $\Delta$ is consistent, then $\Delta$
is consistent. \end{thm}
The compactness theorem can be proven in various ways. One way of
proving it --- although not the most illuminating --- is as a
corollary of the completeness theorem. Indeed, it's not hard to show
that if $\Delta\vdash\phi$, then $\Delta _F\vdash\phi$ for some finite
subset $\Delta _F$ of $\Delta$. Thus, if $\Delta$ is inconsistent,
then $\Delta\vdash\bot$, hence $\Delta _F\vdash\bot$ for a finite
subset $\Delta _F$ of $\Delta$. But then $\Delta _F$ is inconsistent.
\begin{defn} A theory $T$, consisting of axioms $\Delta$ in signature
$\Sigma$, is said to be \emph{complete} just in case $\Delta$ is
consistent, and for every sentence $\phi$ of $\Sigma$, either
$\Delta\vDash \phi$ or $\Delta\vDash \neg \phi$. \end{defn}
Be careful to distinguish between the completeness of our proof system
(which is independent of any theory), and completeness of some
particular theory $T$. Famously, Kurt G{\"o}del proved that the
theory of Peano arithmetic is incomplete, i.e.\ there is a sentence
$\phi$ of the language of arithmetic such that neither $T\vdash\phi$
nor $T\vdash\neg\phi$. However, there are much simpler examples of
incomplete theories. For example, if $\Sigma = \{ p,q\}$, then the
theory with axiom $\vdash p$ is incomplete in $\Sigma$.
\begin{defn} Let $T$ be a theory in $\Sigma$. The \emph{deductive
closure} of $T$, written $\cn{T}$, is the set of $\Sigma$
sentences that are implied by $T$. If $T=\cn{T}$, then we say that
$T$ is \emph{deductively closed}. \end{defn}
\begin{example} Let $\Sigma = \{ p\}$, and let $T = \{ p\}$. Let
$\Sigma '= \{ p,q\}$, and let $T' = \{ p\}$. Here we must think of
$T$ and $T'$ as different theories, even though they consist of the
same sentences, i.e.\ $T=T'$. One reason to think of these as
different theories: $T$ is complete, but $T'$ is incomplete.
Another reason to think of $T$ and $T'$ as distinct is that they
have different deductive closures. For example, $q\vee \neg q$ is
in the deductive closure of $T'$, but not of $T$.
The point here turns out to be philosophically more important than
you might think. Quine argued (correctly, we think) that choosing a
theory is not just choosing axioms, but axioms in a particular
language. Thus, you can't tell what theory a person accepts merely
by examining the sentences that they believe to be
true. \end{example}
\begin{exercise} Show that the theory $T'$ from the previous example
is not complete. \end{exercise}
\begin{exercise} Show that $\cn{\cn{T}}=\cn{T}$. \end{exercise}
\begin{exercise} Consider the signature $\Sigma = \{ p\}$. How many
complete theories are there in this signature? (We haven't been
completely clear on the identity conditions of theories, and hence
on how to count theories. For this exercise, assume that theories
are deductively closed, and two theories are equal just in case they
contain exactly the same sentences.) \end{exercise}
\section{Translating between theories}
Philosophers constantly make claims about relations between theories
--- that they are equivalent, or inequivalent, or one is reducible to
the other, or one is stronger than another. What do all these claims
mean? Now that we have a formal notion of a theory, we can consider
how we might want to represent relations between theories. In fact,
many of the relations that interest philosophers can be cashed out in
terms of the notion of a {\it translation}.
There are many different kinds of translations between theories.
Let's begin with the most trivial kind of translation --- a change of
notation. Imagine that at Princeton, a scientist is studying a theory
$T$. Now, a scientist at Harvard manages to steal a copy of the
Princeton scientist's file, in which she has been recording all the
consequences of $T$. However, in order to avoid a charge of
plagiarism, the Harvard scientist runs a ``find and replace'' on the
file, replacing each occurence of the propositional constant $p$ with
the propositional constant $h$. Otherwise, the Harvard scientist's
file is identical to the Princeton scientist's file.
What do you think: is the Harvard scientist's theory the same or
different from the Princeton scientist's theory?
Most of us would say that the Princeton and Harvard scientists have
the same theory. But it depends on what we mean by ``same''. These
two theories aren't the same in the strictest sense, since one of the
theories contains the letter ``$p$'', and the other doesn't.
Nonetheless, in this case, we're likely to say that the theories are
the same in the sense that they differ only in ways that are
incidental to how they will be used. To borrow a phrase from Quine,
we say that these two theories are \emph{notational variants} of each
other, and we assume that notational variants are equivalent.
Let's now try to make precise this notion of ``notational variants,''
or more generally, of \emph{equivalent theories}. To do so, we will
begin with the more general notion of a translation from one theory
into another.
\begin{defn} Let $\Sigma$ and $\Sigma '$ be propositional signatures.
A \emph{reconstrual} from $\Sigma$ to $\Sigma '$ is a function from
the set $\Sigma$ to the set $\mathsf{Sent}(\Sigma
')$. \end{defn} \noindent A reconstrual $f$ extends naturally to a
function
$\overline{f}:\mathsf{Sent}(\Sigma )\to \mathsf{Sent}(\Sigma ')$, as
follows:
\begin{enumerate}
\item For $p$ in $\Sigma$, $\overline{f}(p)=f(p)$.
\item For any sentence $\phi$, $\overline{f}(\neg \phi )=\neg
\overline{f}(\phi )$.
\item For any sentences $\phi$ and $\psi$, $\overline{f}(\phi\circ\psi
)=\overline{f}(\phi )\circ \overline{f}(\psi )$, where $\circ$
stands for an arbitrary binary connective. \end{enumerate} When no
confusion can result, we use $f$ for $\overline{f}$.
\begin{subthm} For any reconstrual $f:\Sigma\to\Sigma '$, if
$\phi\vdash\psi$ then $f(\phi )\vdash f(\psi )$. \end{subthm}
\begin{proof} Since the family of sequents is constructed inductively,
we will prove this result by induction.
\bigskip\noindent (rule of assumptions) We have $\phi\vdash \phi$ by
the rule of assumptions, and we also have $f(\phi )\vdash f(\phi )$.
\bigskip\noindent ($\wedge$ intro) Suppose that $\phi _1,\phi
_2\vdash \psi _1\wedge \psi _2$ is derived from $\phi _1\vdash \psi
_1$ and $\phi _2\vdash \psi _2$ by $\wedge$ intro, and assume that
the result holds for the latter two sequents. That is, $f(\phi
_1)\vdash f(\psi _1)$ and $f(\phi _2)\vdash f(\psi _2)$. But then
$f(\phi _1),f(\phi _2)\vdash f(\psi _1)\wedge f(\psi _2)$ by
$\wedge$ introduction. And since $f(\psi _1)\wedge f(\psi
_2)=f(\psi _1\wedge \psi _2)$, it follows that $f(\phi _1),f(\phi
_2)\vdash f(\psi _1\wedge \psi _2)$.
\bigskip\noindent ($\to$ intro) Suppose that $\theta \vdash \phi\to
\psi$ is derived by conditional proof from $\theta ,\phi \vdash
\psi$. Now assume that the result holds for the latter sequent,
i.e. $f(\theta ),f(\phi )\vdash f(\psi )$. Then conditional proof
yields $f(\theta )\vdash f(\phi )\to f(\psi )$. And since $f(\phi
)\to f(\psi )=f(\phi\to \psi )$, it follows that $f(\theta )\vdash
f(\phi \to \psi )$.
\bigskip\noindent (reductio) Suppose that $\phi\vdash\neg\psi$ is
derived by RAA from $\phi ,\psi \vdash \bot$, and assume that the
result holds for the latter sequent, i.e. $f(\phi ),f(\psi )\vdash
f(\bot)$. By the properties of $f$, $f(\bot )\vdash \bot$. Thus,
$f(\phi ),f(\psi )\vdash \bot$, and by RAA, $f(\phi )\vdash \neg
f(\psi )$. But $\neg f(\psi )=f(\neg \psi )$, and therefore $f(\phi
)\vdash f(\neg \psi )$, which is what we wanted to prove.
\bigskip\noindent ($\vee$ elim) We leave this step, and the others,
as an exercise for the reader.
\end{proof}
\begin{defn} Let $T$ be a theory in $\Sigma$, let $T'$ be a theory in
$\Sigma '$, and let $f:\Sigma\to\Sigma '$ be a reconstrual. We say
that $f$ is a \textbf{translation} or \emph{interpretation} of $T$
into $T'$, written $f:T\to T'$, just in case:
\[ T\vdash \phi \quad \Longrightarrow \quad T'\vdash f(\phi )
.\] \end{defn}
Note that we have used the word ``interpretation'' here for a mapping
from one theory to another, whereas we previously used that word for a
mapping from a theory to a different sort of thing, viz.\ a set of
truth values. However, there is no genuine difference between the two
notions. We will soon see that an interpretation in the latter sense
is just a special case of an interpretation in the former sense. We
believe that it is a mistake to think that there is some other
(mathematically precise) notion of interpretation, where the targets
are concrete (theory-independent) things.
\begin{disc} Have we been too liberal by allowing translations to map
elementary sentences, such as $p$, to complex sentences, such as
$q\wedge r$? Could a ``good'' translation render a sentence that
has no internal complexity as a sentence that does have internal
complexity? Think about it. \end{disc}
We will momentarily propose a definition for an equivalence of
theories. However, as motivation for our definition, consider the
sorts of things that can happen in translating between natural
languages. If I look up the word ``car'' in my English-German
dictionary, then I find the word ``Auto''. But if I look up the word
``Auto'' in my German-English dictionary, then I find the word
``automobile.'' This is as it should be --- the English words ``car''
and ``automobile'' are synonymous, and are equally good translations
of ``Auto''. A good round-trip translation need not end where it
started, but it needs to end at something that has the {\it same
meaning} as where it started.
But how are we to represent this notion of ``having the same
meaning''? The convicted Quinean might want to cover his eyes now, as
we propose that a theory defines its own internal notion of sameness
of meaning. (Recall what we said in the preface: that first-order
metatheory is chalk full of intensional concepts.) In particular,
$\phi$ and $\psi$ have the same meaning relative to $T$ just in case
$T\vdash \phi\lra\psi$. With this notion in mind, we can also say
that two translations $f:T\to T'$ and $g:T\to T'$ are synonymous just
in case they agree up to synonymy in the target theory $T'$.
\begin{defn}[equality of translations] Let $T$ and $T'$ be theories,
and let both $f$ and $g$ be translations from $T$ to $T'$. We write
$f\simeq g$ just in case $T'\vdash f(p)\leftrightarrow g(p)$ for
each atomic sentence $p$ in $\Sigma$. \end{defn}
With this loose notion of identity of translations, we are ready to
propose a notion of an equivalence between theories.
\begin{defn} For each theory $T$, the identity translation
$1_T:T\to T$ is given by the identity reconstrual on $\Sigma$. If
$f:T\to T'$ and $g:T'\to T$ are translations, we let $gf$ denote the
translation from $T$ to $T$ given by $(gf)(p)=g(f(p))$, for each
atomic sentence $p$ of $\Sigma$. Theories $T$ and $T'$ are said to
be \emph{homotopy equivalent}, or simply \emph{equivalent}, just in
case there are translations $f:T\to T'$ and $g:T'\to T$ such that
$gf\simeq 1_T$ and $fg\simeq 1_{T'}$. \label{df:hom} \end{defn}
\begin{exercise} Prove that if $v$ is a model of $T'$, and $f:T\to T'$
is a translation, then $v\circ f$ is a model of $T$. Here $v\circ
f$ is the interpretation of $\Sigma$ obtained by applying $f$ first,
and then applying $v$. \end{exercise}
\begin{exercise} Prove that if $f:T\to T'$ is a translation, and $T'$
is consistent, then $T$ is consistent. \end{exercise}
%%% Local Variables:
%%% mode: latex
%%% TeX-master: "main"
%%% End: